2013
DOI: 10.1080/17535069.2013.808432
|View full text |Cite
|
Sign up to set email alerts
|

Displacement and urban restructuring in Amsterdam; following relocatees after demolition of social housing

Abstract: Over the past decade, urban restructuring of segregated neighbourhoods has transformed many urban districts, in the Netherlands and elsewhere; middle class households have entered neighbourhoods which were previously inhabited by lower class. Some argue that this influx of middle-class has happened at the expense of the displaced original population. We investigated this process of (forced) relocation from restructured neighbourhoods. In contrast with earlier studies, individual level data has been provided di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
6
0
3
Order By: Relevance
“…In all, 12 articles found that displaced households move to surrounding areas. Out of these, 9 studied displacement following urban restructuring (Goetz 2002;Clampet-Lundquist 2004;Oakley & Burchfield 2009;Bolt & Van Kempen 2010;Doff & Kleinhans 2011;Kleit & Galvez 2011;Oakley et al 2013;Tieskens & Musterd 2013;Lawson et al 2015;Dragan et al 2020), of which 3 suggested that these destination outcomes are spatially clustered in disadvantaged neighbourhoods (Goetz 2002;Oakley & Burchfield 2009;Oakley et al 2013). The 3 remaining articles studied displacement following gentrification, emphasizing that lowstatus households generally make short distance moves (Dragan et al 2020, p. 6;Lyons 1996, pp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 12 articles found that displaced households move to surrounding areas. Out of these, 9 studied displacement following urban restructuring (Goetz 2002;Clampet-Lundquist 2004;Oakley & Burchfield 2009;Bolt & Van Kempen 2010;Doff & Kleinhans 2011;Kleit & Galvez 2011;Oakley et al 2013;Tieskens & Musterd 2013;Lawson et al 2015;Dragan et al 2020), of which 3 suggested that these destination outcomes are spatially clustered in disadvantaged neighbourhoods (Goetz 2002;Oakley & Burchfield 2009;Oakley et al 2013). The 3 remaining articles studied displacement following gentrification, emphasizing that lowstatus households generally make short distance moves (Dragan et al 2020, p. 6;Lyons 1996, pp.…”
Section: Resultsmentioning
confidence: 99%
“…There are 5 articles that find that relocation enhances the dispersal of both poverty and ethnic groups (Boston 2005;Kingsley et al 2003;Goetz 2010;Tieskens & Musterd 2013;Lopez & Greenlee 2016). The articles that found that displacement reduced income segregation all studied relocation following urban restructuring (Kingsley et al 2003;Boston 2005;Bolt et al 2009;Popkin et al 2009;Bolt & Van Kempen 2010;Goetz 2010;Sink & Ceh 2011;Tieskens & Musterd 2013;Lopez & Greenlee 2016). Interestingly, 4 of these studies argued that the effects of poverty de-concentration are limited due to the impoverished state of the origin neighbourhood (Kingsley et al 2003;Goetz 2010;Sink & Ceh 2011;Tieskens & Musterd 2013).…”
Section: Displacementmentioning
confidence: 99%
“…Dünyada en bilindik yeniden yapılandırma uygulamaları olan Hope VI, The Big City Policies, The New Deal for Communities literatürde olumlu ve olumsuz sonuçlarıyla birlikte ele alınmaktadır. Özellikle yer değiştirmeler sonrasında konut edinme fırsatlarının doğması, konut ve mahallenin fiziksel durumlarının iyileştirilmesi bu programların pozitif sonuçlarına örnek gösterilmektedir (Kleinhans, 2003;Kleinhans & Van Der Laan Bouma-Doff, 2008;Bolt & Van Kempen, 2010;Kearns & Mason, 2013;Tieskens & Musterd, 2013;Miltenburg vd., 2018). Diğer taraftan projelere dair eleştirilerin odaklandığı noktalar yerinden edilme süreçlerinin en tartışmalı konuları olan toplumsal ilişkilerde zayıflama, yer değiştirmeye bağlı yaşanan stres gibi durumların ortaya çıkmasıdır (Hankins, 2014;Lees & Ferreri, 2016).…”
Section: Soylulaştırma Yerinden Edilme Ve Kentsel Dönüşüm Projeleriunclassified
“…Olumlu yöndeki tutumun nedenlerinin başında konut kalitesi ve yaşam kalitesinin artması gösterilmektedir. Esasında bu durum literatürde çeşitli araştırmacıların kentsel dönüşüm projelerine dair vurguladıkları pozitif yöndeki gelişimle paralel bir çıktıdır (Kearns & Mason, 2013;Tieskens & Musterd, 2013;Miltenburg, vd., 2018) Görüşmelerin ikinci teması Projeye Dair Toplumsal Bağ ve Bağlantılardır. Bu durum aynı zamanda kentsel dönüşüm projelerinin en tartışmalı etkilerden olan komşuluk ilişkilerinin negatif yöndeki değişimiyle paralel bulgular ortaya çıkarmıştır (Hankins, 2014;Lees & Ferreri, 2016;Demir, 2021)…”
Section: 2kentsel Dönüşümden Memnuniyet Ve Yeni Yer Seçimindeki Krite...unclassified
See 1 more Smart Citation